Psychosocial Background History of Pregnant Women with Opioid Use Disorder: A Prospective Cohort Study - Towers, Craig V.; Katz, Emily; Liske, Emily; Hennessy, Mark; Wolfe, Lynlee; Visconti, Kevin (American Journal of Perinatology, 2020)
Objective This study aimed to evaluate the psychosocial background history and confounding social factors in pregnant women with opioid use disorder (OUD).Study Design We performed a prospective observational cohort study of pregnant women from a dedicated obstetrical OUD clinic. Data collection came from extensive interview sessions regarding psychosocial background events and other social factors that might impact prenatal care.Results From February 1, 2017, through September 30, 2018, 411 pregnant women were evaluated and 294 (72%, 95% confidence interval [CI]: 67–76%) reported abuse of which 217 (53%, 95% CI: 48–58%) involved sexual abuse (prior to the age of 13 years in 54% of cases) and 209 (51%, 95% CI: 46–56%) involved cases of other physical abuse. Only 10% reported habitual opioid use for managing chronic pain. Only 9% had a valid driver's license with access to a car making transportation to office visits difficult.Conclusion A history of abuse (mainly sexual and/or physical) appears to be the main precipitating event leading to OUD in our pregnant population. Transportation was the primary social factor limiting access to prenatal care. For primary prevention to be successful in our region, early identification of young women who have experienced abuse needs to occur followed by psychotherapy health care intervention before opioid drugs are used.
Keywords: abuse in females; opioid use disorder; sexual abuse; physical abuse; chronic pain; marijuana abuse